Effects of Ecologically‐Based Family Therapy with substance‐using, prostituting mothers. Issue 4 (20th July 2017) - Murnan, Aaron; Wu, Qiong; Slesnick, Natasha
Abstract: Studies report that high rates of prostituting women seek substance use treatment, and that most of these women have children in their care. However, compared to non‐prostituting women, they show poorer treatment outcomes. Effective intervention for this population is needed, and the current study is the first to test family therapy with mothers seeking substance use treatment, who also reported prostitution. Sixty‐eight treatment‐seeking women with children in their care were randomly assigned to receive twelve sessions of Ecologically‐Based Family Therapy or twelve sessions of individual treatment. Results showed that women who received family therapy reported greater reductions in substance use and depressive symptoms as well as greater improvements in their mother‐child interactions. Findings underscore the importance of offering family therapy as a treatment option when prostituting women with children seek substance use treatment. Practitioner points: It has proved difficult to meet the unique needs of prostituting women, and this article offers practical assistance to practitioners serving this population Ecologically‐Based Family Therapy (EBFT) shows promise, having some superior outcomes compared to an individual therapy with prostituting mothers Substance use treatment facilities should strongly consider including EBFT for these women and their children as an adjunct to treatment